If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9 + -6) + y = 12 Combine like terms: 9 + -6 = 3 2(3) + y = 12 Multiply 2 * 3 6 + y = 12 Solving 6 + y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 12 + -6 Combine like terms: 6 + -6 = 0 0 + y = 12 + -6 y = 12 + -6 Combine like terms: 12 + -6 = 6 y = 6 Simplifying y = 6
| 4(x+9)=3(x-8)+x | | -2(t+2)+5*t=6t+11 | | 5s+17=157 | | 7h+4=7 | | 2.4=2+0.3x | | 7p^2+6=0 | | X-4x=231 | | 2cosx=x | | 4*(d-3)=2d | | 9x-2y=-18 | | 8x^3-28x+29=0 | | 93+12m=3(4m-1) | | W^2+w+56= | | 6cos^2x-7cosX-10=0 | | 13=10n+6 | | 15*m=5 | | x+ln((x^2)-4)=0 | | 2x^2+12x+50=0 | | 2-4=4(2)-10 | | 4+7f=4 | | 120x+320=30-(x-3) | | q*q=15+1 | | factorx^2+12x+2=0 | | 120x+320=0.3-(x-3) | | 100x+700=60(x-3) | | 10x+35=6-(x-3) | | p*p=1 | | 36+32=13-(x-3) | | 7r+2=5(r-4)whatisx | | 5x(3x+5)=10 | | w=21+2p | | 3.2x+14=-4 |